INVESTIGATION OF DEFORMATION AND MICROSTRUCTURE OF BAINITE IN Cu-9.97%Al-4.62%Mn ALLOY - Emine ALDIRMAZ; Ilhan AKSOY (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
In this study, some physical and mechanical properties in Cu-9.97%Al-4.62%Mn (Wt) alloy were investigated by X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and compression deformation test. Bainite phase were obtained in the samples according to SEM and XRD analyses. Compression stress was applied on the alloy in order to investigate the deformation effect on the bainite phase transformation. On the surface of the Cu-9.97%Al-4.62%Mn alloy after the deformation, both bainite and martensite variants formed.